Identifikasi Faktor-Faktor Diskriminasi Gender yang Mempengarrhi Karir Karyawan Wanita di Kota Yogyakarta - Rr. Nurasih; Agustini Dyah Respati (Jurnal Riset Manajemen dan Bisnis, 2007)
Statistically, the number of women who works outside household is getting increase. As a part of worfforce, woman not only takes a position as general employee but they are also employed as a manager. It indicates that woman plays an important role in organization. In other words it can be said that the globol labor force has changed. Change in labor force involved an aging worfforce and a diverse worffirce. Furthermore diversity exists within labor force. As a result organizations cannot afford to ignore or discount the potential contributions of wornen. At the same time work opportunity for women is also more available. Women, howqer find dfficulties that hinder them in pursuing a success in career. This hindrances result fro* the social and culture concept that the nature of a woman is a houssvyife. In fact women who hold a dual career hme a more responsibility either to their emplolters or to their household. Being a dual career people, women show a high work motivation and good performance. This paper examines the affecting factorson wornen coreer in term of sex discrimination that is discrimination on grounds of gender. The result shows that there are five gender discrimination factors affecting woman career.Kqtwords : woman car e er, gender, divers ity, culture, dis crimination.